Les écarts de revenus dans les espaces transfrontaliers. Des moteurs de la mobilité transfrontalière - Belkacem, Rachid (Borders in Perspective UniGR-CBS Thematic Issue. Grenzüberschreitende Ungleichheiten in der Großregion | Inégalités transfrontalières dans la Grande Région, 2025)
Abstract: „This article analyses wage disparity in cross-border spaces in the Greater Region (GR) and Upper Rhine. It is based on the results of two studies, the first funded by EURopean Employment Services-Greater Region (EURES-GR) in 2022 and the other, ongoing, funded by EURopean Employment Services-T Upper Rhine. The analysis shows that this disparity can be explained by various economic, sociological and institutional factors, which operate on various levels: micro (relating to corporate policies), macro (relating to national taxation and social security policy) and meso (relating to economic sectors and branches). It begins by showing that salaries and their various component parts are hard to define, making cross-border comparison difficult. It then signals that while wages in Switzerland and Luxembourg are very attractive, they must be balanced against the cost of living and working hours, which differ on each side of the border. The main takeaway from this analysis is that the gap between wages and the cost of living is a significant driver of cross-border working in border regions.“
Keywords: Arbeitnehmer; Arbeitsmarkt; Arbeitsmigration; Grenzarbeitnehmer; Lohnniveau; Mobilität; Schweiz; Wohnen; Wohnungsmarkt

Introduction. Cross-Border Inequalities. An Exploration in the Greater Region - Connor, Ulla; Aubry, Lola (Borders in Perspective UniGR-CBS Thematic Issue. Grenzüberschreitende Ungleichheiten in der Großregion | Inégalités transfrontalières dans la Grande Région, 2025)
Keywords: Arbeitnehmer; Arbeitsmarkt; Arbeitsmigration; Grenzarbeitnehmer; Mobilität; Wohnen; Wohnungsmarkt

Grenzüberschreitende Ungleichheiten in der Großregion. Perspektiven und Daten - Himbert, Alexa (Borders in Perspective UniGR-CBS Thematic Issue. Grenzüberschreitende Ungleichheiten in der Großregion | Inégalités transfrontalières dans la Grande Région, 2025)
Abstract: „Seit über 20 Jahren sammelt und analysiert die Interregionale Arbeitsmarktbeobachtungsstelle (IBA·OIE) im Auftrag der politischen Verantwortlichen der Großregion vergleichbare und interpretierbare Daten über den Arbeitsmarkt auf dem Gebiet der Großregion und liefert damit die Grundlage für struktur- und arbeitsmarktpolitische Entscheidungen in der Großregion. Durch die lange und kontinuierliche Beobachtung gelingt es, ein deutliches Bild der Pendlerbewegungen und ihrer Profile im Kooperationsraum der Großregion zu zeichnen und diese engen Verflechtungen sichtbar zu machen. Allerdings werden auch die Unterschiede deutlich, die kulturell bedingt, aber auch durch die heterogenen Wirtschaftsstrukturen der Teilregionen gewachsen sind. Als Grundlage dienen zunächst die Daten der europäischen Statistikbehörde Eurostat, die in harmonisierter Form vorliegen und dadurch im grenzüberschreitenden Kontext leicht vergleichbar sind. Für die detaillierteren Indikatoren auf der Ebene der Großregion werden zudem die Daten der jeweiligen statistischen Ämter und anderer Datenproduzenten aus den Teilregionen herangezogen. Aufgrund unterschiedlicher Hintergründe und Erhebungsmethoden bedürfen die Zahlen einer deutlichen Kontextualisierung und meist einer Harmonisierung. Insbesondere die Daten zu den Grenzgängerströmen stammen aus unterschiedlichen Datenquellen, die einer Harmonisierung auf großregionaler Ebene bedürfen.“
Keywords: Arbeitsmarkt; Arbeitsmigration; Grenzarbeitnehmer

Les travailleurs frontaliers atypiques face aux inégalités transfrontalières. Éclairages et défis - Mezaroş, Mădălina; Uyttebrouck, Constance; Górczyńska-Angiulli, Magdalena; Paccoud, Antoine (Borders in Perspective UniGR-CBS Thematic Issue. Grenzüberschreitende Ungleichheiten in der Großregion | Inégalités transfrontalières dans la Grande Région, 2025)
Abstract: „This article explores the dynamics of atypical cross-border workers in the Greater Region, that is to say, those who reside in a neighbouring country while maintaining employment in Luxembourg. Before highlighting the housing access inequalities that this residential dynamic entails, the analysis examines housing policies in Belgium, France, Germany and Luxembourg to better understand the disparities that intensify pressure on regional housing markets. Recent and historical data on the profiles of atypical cross-border workers are presented, along with testimonies from former residents of Luxembourg who have left the country. The study sheds light on how border housing markets respond to this growing demand, sometimes to the detriment of long-standing residents. It concludes by emphasising the need for a cross-border housing observatory to co-ordinate data collection and assess emerging inequalities, including land pressures and residential exclusion in border areas, calling for more harmonised governance to address these challenges.“
Keywords: Arbeitnehmer; Arbeitsmarkt; Arbeitsmigration; Grenzarbeitnehmer; Wohnen; Wohnungsmarkt

Marché du travail transfrontalier. Différentiels et interdépendances - Pigeron-Piroth, Isabelle; Schiel, Kerry (Borders in Perspective UniGR-CBS Thematic Issue. Grenzüberschreitende Ungleichheiten in der Großregion | Inégalités transfrontalières dans la Grande Région, 2025)
Abstract: „With its 267,300 cross-border workers in 2022, the Greater Region of SaarLorLux is often presented as a model of European integration. Borders are becoming less and less perceptible, and are disappearing for commuters travelling from one country to another. However, the Covid-19 pandemic has shown the reappearance of borders that were thought to have been forgotten. It has to be said that many border-related issues have come to the fore in recent years, all the more so because of the many challenges and tensions as well as the growing number of cross-border workers. The question of inequalities is central in this context of a cross-border labour market with strongly interwoven components.“
Keywords: Arbeitnehmer; Arbeitsmarkt; Arbeitsmigration; Grenzarbeitnehmer

« Je travaille au Luxembourg ». Une socio-histoire d'un espace transfrontalier de qualification - Deshayes, Jean-Luc (Presses universitaires de Nancy, 2021)
Aus dem Inhaltstext: „À la question « Qu'est-ce que tu deviens? », les habitants des zones frontalières françaises du Luxembourg, qui pour parfois plus de la moitié de la population active travaillent au Grand-Duché voisin, répondent souvent: « Je travaille au Luxembourg » comme si le lieu d’emploi devenait plus important que la profession ou le contenu du travail. L’analyse s’appuie sur des recherches ancrées dans le bassin de Longwy sur plus de 40 ans dans trois secteurs du travail frontalier: la sidérurgie, la banque et le travail social.“
Inhaltsverzeichnis: http://bvbr.bib-bvb.de:8991/exlibris/aleph/a23_1/apache_media/72L5DGMASI4HEYX9VEG1PMGRVXBGL5.pdf
Keywords: Arbeitsmarkt; Grenzarbeitnehmer; Longwy (Region); Regionale Mobilität

Métropole européenne de Lille (MEL). Construire une politique de l’emploi dans un cadre transfrontalier - Cassette, Bruno; Jodogne, Simon; Vaillant, David (Annales des Mines - Réalités industrielles, 2020)
Abstract: „La Métropole européenne de Lille (MEL) est confrontée à un chômage structurel avec des taux élevés, notamment dans le versant nord-est de son territoire (Roubaix-Tourcoing), à proximité de la frontière franco-belge. La MEL a, dès le début des années 2000, pris l’initiative de développer des politiques en faveur de l’emploi par des actions économiques, sociales et d’aménagement de son territoire. Frontalière de la Belgique, en particulier de la Flandre belge, qui connaît une situation de plein emploi, la MEL a souhaité, en 2018, aller plus loin, en cherchant à mieux comprendre les caractéristiques socio-économiques, les modes de fonctionnement du système flamand et ses performances pour renforcer ses politiques métropolitaines en faveur de l’emploi. Cette stratégie métropolitaine complète et s’insère dans un ensemble de dispositifs et d’actions transfrontalières visant à décloisonner le marché de l’emploi et à développer une Eurométropole Lille-Kortrijk-Tournai, de manière plus intégrée.“
Keywords: Arbeiterbewegung; Arbeitsmarkt; Eurométropole Lille-Kortrijk-Tournai; Grenzarbeitnehmer; Grenzgebiet; Grenzüberschreitende Kooperation; Lille; Roubaix; Tourcoing

Zo dicht bij elkaar, maar toch heel anders. Eigendomsverhoudingen, productie en werkgelegenheid in de vier mijnbouwgebieden in het Maas-Rijngebied - Knotter, Ad (Studies over de sociaal-economische geschiedenis van Limburg/Jaarboek van het Sociaal Historisch Centrum voor Limburg, 2016)
Keywords: Arbeitsmarkt; Arbeitsmigration; Euregio Maas-Rhein; Grenzarbeitnehmer; Grenzgebiet; Steinkohlenbergbau

Grenzüberschreitende Arbeitsmarktpolitik. Institutionen und institutionelle Steuerung des Arbeitsmarktes in der Großregion SaarLorLux-Rheinland-Pfalz-Wallonien - Albrecht, Maria; Meyer, Wolfgang (Grenzüberschreitendes Arbeiten in der Großregion SaarLorLux, 2012)
Keywords: Arbeitsmarkt; Grenzarbeitnehmer; Internationale Mobilität; Saar-Lor-Lux

Transnationale Netzwerke und Institutionen in der Großregion SaarLorLux - Bähr, Holger; Schenke, Hanna; Filsinger, Dieter (Grenzüberschreitendes Arbeiten in der Großregion SaarLorLux, 2012)
Keywords: Arbeitsmarkt; Grenzarbeitnehmer; Internationale Mobilität; Saar-Lor-Lux

Grenzüberschreitendes Arbeiten in der Großregion SaarLorLux - Meyer, Jürgen; Rampeltshammer, Luitpold (Universaar, 2012)
Inhaltsverzeichnis: https://d-nb.info/1026984491/04
Keywords: Arbeitsmarkt; Grenzarbeitnehmer; Internationale Mobilität; Saar-Lor-Lux

Lebenslanges Lernen in der Großregion. Grenzenlose Weiterbildung für Pflegekräfte? - Schäfer, Désirée; Renaud, Dagmar; Riemer-Hommel, Petra (Grenzüberschreitendes Arbeiten in der Großregion SaarLorLux, 2012)
Keywords: Altenpflege; Arbeitsmarkt; Berufsbildung; Bildungswesen; Grenzarbeitnehmer; Internationale Mobilität; Krankenpflege

Buitenbeentjes. Nederlandse kompels in de Luikse kolenmijnen na de Tweede Wereldoorlog - Rutten, Willibrord (Studies over de sociaal-economische geschiedenis van Limburg/Jaarboek van het Sociaal Historisch Centrum voor Limburg, 2011)
Keywords: Arbeitsmarkt; Arbeitsmigration; Grenzarbeitnehmer; Lüttich; Steinkohlenbergbau

Regional labour markets and international migration in twentieth-century Europe. The cases of coal mining in Liège (B) and Limburg (NL) compared - Langeweg, Serge; Roels, Leen; Knotter, Ad (Mitteilungsblatt des Instituts für Soziale Bewegungen. Forschungen und Forschungsberichte, 2008)
Keywords: Arbeitsmarkt; Arbeitsmigration; Grenzarbeitnehmer; Lüttich; Steinkohlenbergbau; Südlimburg (Niederlande)

Werken over de grens. Limburgers naar Duitsland, 1870–1914 - Langeweg, Serge (Studies over de sociaal-economische geschiedenis van Limburg/Jaarboek van het Sociaal Historisch Centrum voor Limburg, 2002)
Keywords: Arbeitsmarkt; Arbeitsmigration; Deutschland; Grenzarbeitnehmer; Provinz Limburg (Niederlande)

Significant insignificance. Boundaries in a borderless European Union. Deconstructing the Dutch–German transnational labour market - Strüver, Anke (Journal of Borderlands Studies, 2002)
Abstract: „This contribution elaborates on European Union (E.U.) geopolitical discourses, which attempt to overcome the ‘insignificance’ of state‐borders through the establishment of cross‐border regions. Drawing on the nonexisting Dutch‐German transnational labor market as an example, the observed ‘non‐practice’ of border crossing is introduced. ‘Significant boundaries’ and their meanings, on the other hand, are constructed by narratives and images that are not only representations, but also actively shape people's everyday life. The effects of these boundary narratives are analyzed in terms of ‘cognitive distance’, defined both as the creation of a barrier effect and the ignorance of what lies beyond, expressed as a boundary in people's minds.“
Keywords: Arbeitsmarkt; Europäische Integration; Grenzarbeitnehmer; Grenzgebiet; Grenzüberschreitende Kooperation